Some Properties related N-Functions with Young’s Inequality - Kadhim, Dhuha Abdul ameer (Al-Qadisiyah Journal of Pure Science, 2017)
In this paper, we will summarize the necessary facts about a special class of convex functions called N-functions and introduce some theorems related N-functions and complementary N-functionswith Young’s inequality.